Full intermetallic joints for chip stacking by using thermal gradient bonding. (July 2016) - Yang, T.L.; Aoki, T.; Matsumoto, K.; Toriyama, K.; Horibe, A.; Mori, H.; Orii, Y.; Wu, J.Y.; Kao, C.R.
Abstract: Solid-liquid interdiffusion bonding is a promising process for three dimensional chip stacking, but nevertheless is plagued with low throughput. A new solid-liquid interdiffusion bonding process, with much higher bonding speed, is proposed in this study. Instead of using a homogeneous bonding temperature, a temperature gradient is superimposed across the joint in the new process, which possesses many advantages. Firstly, the new process is 3–10 times faster, depending on the bonding parameters. Secondly, columnary Cu6 Sn5 grains grow from the cold-end to the hot-end, with the crystallographic orientation of Cu6 Sn5 preferentially aligned along the (0001) pole. Lastly, the new process consumes very little Cu substrate at the cold-end due to the fact that most of the Cu atoms are from the hot-end. The mechanism for the new process is proposed and experimentally verified in this study. Graphical abstract: